V-isoNet: A virtualised and isolated network using open source technologies - Gleeson, M.; Markey, D.; Mtenzi, F. (Journal of Digital Information Management, 2010)
Computer Security and Forensics is an emerging academic discipline in which there are many challenges facing educational institutions in teaching, from both an educational and technical perspective. The School of Computing in Dublin Institute of Technology offers two Security and Forensic Computing modules, a 4th year BSc (Hons) module and an MSc module. Currently the BSc module requires a practical section to the course while the MSc module does not require practical work. In order to aid teaching during the next semester, both sets of students will be exposed to a Security and Forensics practical laboratory. This series of research proposes a phased approach to design and establish a suitable overall environment to provide a comprehensive Computer Security and Forensics practical laboratory. The three identifiable components are (1) an isolated networked environment, (2) an exposed repository to be used to demonstrate vulnerabilities and (3) the formation of a Security and Forensics toolkit to be used in conjunction with the isolated network environment and the exposed repository. This first paper, in a series of three, will introduce the reader to the overall research objective. It will then focus on research and development of the first identified component, namely an isolated network environment.
Keywords: Education; Forensics; Isolated; Network; Open source; Security; Virtualization